Behavioral Implementation - de Clippel, Geoffroy (American Economic Review, 2014)
Implementation theory assumes that participants' choices are rational, in the sense of being consistent with the maximization of a context-independent preference. The paper investigates implementation under complete information when individuals' choices need not be rational. (JEL D11, D60, D83, R31)